The Role of a Longitudinal, Multidisciplinary Clinic in Building a Unique Research Collaborative - Gonzales, Alexandria A.; Mastrolonardo, Alexander; Winget, Kenna; Ragulojan, Malavan; Fleming, Adam J.; Singh, Sheila K. (Frontiers in Oncology, 2022)
Multidisciplinary neuro-oncology clinics allow collaboration between various specialties and training levels. Building a tenable clinical research program based in the longitudinal dialogue and practice of collaborative clinicians and trainees can bridge clinical observations to research execution. However, forming a research team around a multidisciplinary clinic’s activities is constrained by a lack of literature or guidelines. As well, challenges in sustaining team logistics, communication, and productivity can persist without a standardized team framework. This perspective discusses the state of research teams in clinical oncology, and uses experiences from the McMaster Pediatric Brain Tumour Study Group to guide those seeking to form a research team based on the collective activities and observations of a multidisciplinary clinic.